Deni PENGGUNAAN MEDIA VIDEO AKUN INSTAGRAM INFOJAWABARAT DALAM MENINGKATKAN DAYA KREATIVITAS SISWA KELAS X SMA - Deni; Fahruroji, Fahruroji; Apriliyani, N Yeffa Afnita (Dharmas Education Journal (DE_Journal), 2023)
Students still need help writing poetry because they cannot determine a theme or image to use as inspiration. This study aimed to determine whether class X students of SMA Negeri 25 Bandung in the 2022/2023 academic year can write poetry more creatively, thanks to video content from the Instagram infojawabarat account. The true experimental design method was used in this study. The pretest-posttest control group design was used in this study. Based on the calculation results of the Normality Test, abnormal Significance data is generated. Then test the hypothesis using the Wilcoxon test; it is known that the output test Statistics is known as Asymp. Sig. (2-tailed) is 0.001. Because the value of 0.001 <0.05, "Hypothesis accepted." Furthermore, a homogeneity test was carried out using the Mann-Whitney Test. Based on the output of Test Statistics, it is known that the value of Asymp Sig. (2-tailed) of 0.004 < 0.05 "Hypothesis accepted." So it can be concluded that there is a difference between the experimental class and the control class in terms of students' creative results, and the use of video content on the Instagram account infojawabarat has an impact on increasing students' creativity.